The Effectiveness of Telenursing to Improve the Quality of Life of Coronary Artery Disease Patients: Systematic Review - Holifah, Ketut; Herawati, Tuti (Indonesian Journal of Global Health Research, 2024)
The quality of life in coronary artery disease (CAD) patients generally decreases. Nurses need to carry out comprehensive nursing interv The quality of life in coronary artery disease (CAD) patients generally decreases. Nurses need to carry out comprehensive nursing interventions even though the client has been discharged from the hospital or at home. Telenursing is one of the nurse efforts to provide nursing care remotely, especially education and monitoring of CAD patients. This literature study aims to see the effectiveness of implementing telenursing on the condition of CAD patients which has implications for the patient's quality of life. The database was collected from open source online journals including Pubmed, Science Direct, Proquest, Clinical Key Nursing, and Willey Online Library. Articles were searched using the keywords telenursing, telemonitoring, teleeducation, quality of life, and coronary artery disease. The articles used were articles from the last 5 years from 2019 to 2024 with an initial number of 241 and 9 articles analyzed. Forms of telenursing in this literature study include application-based telenursing, telephone reminders, telephone follow-up and via messages. All research studies in the study show that telenursing has a significant impact on the quality of life of CAD patients. All types of telenursing have an impact on the patient's quality of life. Nurses with support from the government are expected to be able to implement comprehensive and integrated telenursing with cardiac rehabilitation programs to improve the quality of life for CAD patients. entions even though the client has been discharged from the hospital or at home. Telenursing is one of the nurses efforts to provide nursing care remotely, especially education and monitoring of CAD patients. This literature study aims to describe the effect of telenursing on quality of life in CAD patients. The database was collected from open source online journals including Pubmed , Science Direct, Proquest, Clinical Key Nursing, and Willey Online Library. Articles were searched using the keywords telenursing, telemonitoring, teleeducation, quality of life, and coronary artery disease. Forms of telenursing in this literature study include application-based telenursing, telephone reminders, telephone follow-up and via messages. All research studies in the study show that telenursing has a significant impact on the quality of life of CAD patients. All types of telenursing have an impact on the patient's quality of life. Nurses with support from the government are expected to be able to implement comprehensive and integrated telenursing with cardiac rehabilitation programs to improve the quality of life for CAD patients. Kualitas hidup pada pasien coronary artery disease (CAD) umumnya mengalami penurunan. Perawat perlu melakukan intervensi keperawatan yang komperehensif meskipun klien sudah keluar rumah sakit atau dirumah. Telenursing merupakan salah satu upaya perawat untuk memberikan asuhan keperawatan dengan jarak jauh, khususnya edukasi dan monitoring pada pasien CAD. Studi literature ini bertujuan untuk menggambarkan pengaruh telenursing terhadap kualitas hidup pada pasien CAD. Database dikumpulkan dari jurnal online open source meliputi Pubmed, Science Direct, Proquest, Clinical Key Nursing, dan Willey Online Library. Artikel dicari menggunakan kata kunci telenursing, telemonitoring, teleeducation, quality of life, dan coronary artery disease. Bentuk telenursing dalam studi literature ini antara lain telenursing berbasis aplikasi, telephone reminder, follow up telephone dan melalui pesan. Semua studi penelitian dalam studi menunjukkan bahwa telenursing memiliki pengaruh yang signifikan terhadap kualitas hidup pasien CAD. Semua jenis telenursing yang memiliki pengaruh terhadap kualitas hidup pasien. Perawat dengan dukungan dari pemerintah diharapkan dapat menerapkan telenursing yang komperehensif dan terintegrasi dengan program rehabilitasi jantung untuk meningkatan kualitas hidup pada pasien CAD